Effects of Viscous Dissipation on Unsteady Mixed Convection Heat Transfer from a Circular Cylinder for Parallel and Contra Flows - Al-Rashed, Abdullah A. A. A.; Roy, Nepal C.; Hossain, Md. Anwar (Frontiers in Mechanical Engineering, 2017)
Unsteady mixed convection heat transfer from a circular cylinder has been investigated in the presence of viscous dissipation. The isothermal horizontal cylinder is placed to the oncoming free stream whose direction is considered in the free convection flow (parallel flow) and opposite to it (contra flow). The system of dimensionless governing equations for unsteady, two-dimensional flow is reduced to a suitable form for integration and the resulting equations are solved employing finite difference method. For both parallel and contra flows the influences of the viscous dissipation on the Nusselt number are found to be strong, however, it has rather weak effect on the vorticity distribution. In the presence of the viscous dissipation, the isotherms are significantly changed while there is less effect on the streamlines. Under the same conditions, the size of the vortex for the contra flow is larger than that for parallel flow.